Penguatan Strategi Pencegahan Stunting Melalui Pendidikan Keluarga Pada Desa Sugai Kakap Kecamatan Sungai Kakap Kabupaten Kubu Raya - Martoyo; Nahot Tua Parlindungan Sihaloho; Bima Sujendra; Nawang Aviani (Empowerment: Jurnal Pengabdian Masyarakat, 2023)
This service activity is entitled Socialization of Stunting Prevention Through Family Education in Sungai Kakap Village, Sungai Kakap District, Kubu Raya Regency. This activity aims to educate the public regarding the Government's Program on Stunting Prevention through education in the family environment by educating the public about the importance of providing balanced nutrition to 100 HPK. This socialisation activity uses lecture, question and answer, and discussion methods. The socialisation participants were the Head of Sungai Kakap Village, the Sungai Kakap Village PKK group and the Sungai Kakap Village Office Staff of approximately 30 people. The socialisation results show that the Village Government and the Sungai Kakap Village Community welcomed the implementation of the PKM activity to build public awareness of the importance of 100 HPK in preventing stunting. Raising public awareness of the 100 HPKs and educating the public about stunting prevention must start with family education.